Rancang Bangun Sistem Prediksi Kebutuhan Bahan Makanan Berbasis Web (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Abstract Prediction of food supplies is an activity of estimating the stock of foodstuffs that will be sold at a certain time, the supply of foodstuffs is determined by the estimation of future needs so that the seller can make the appropriate provision. When sales are predicted accurately, the fulfillment of consumer needs can be managed on time, the seller's cooperation with the relationship is maintained properly, customer satisfaction is met, the seller can overcome the loss of shortages or out of stock, prevent food ingredients from becoming damaged or stale. On the other hand, the seller can determine policy decisions on production plans, inventory, asset investment and cash flow. In other words, no salesperson can avoid estimating or forecasting sales for the purposes of planning the activities that must be carried out. Based on research conducted through application development in the form of a website displaying the results of sales of raw food ingredients based on time series data, the accuracy results obtained with an accuracy rate of 80% and through a black box evaluation it was found that the application has been running very well with a high level of respondents. shows a true value of 90% in the application that has been made. Keyword : forecasting, time series, web application, sales, raw food ingredients.